THE IMPLEMENTATION PROBLEM OF VILLAGE FUND UNCONDITIONAL CASH TRANSFER DISTRIBUTION IN SIDOARJO REGENCY DURING COVID-19 PANDEMIC - Bagus Nuari Harmawan; Richul Munawaroh; Annis Oktaviani; Rinda Purwati (Fakultas Politik Pemerintahan IPDN, 2023)
Abstract The Covid-19 pandemic has impeded economic activity, reduced the number of employees, and lessened purchasing power, potentially diminishing the well-being of the population. It led to an increase in the number of impoverished individuals and families in Indonesia, particularly in Jedong Cangkring Village, Sidoarjo Regency. This study attempts to determine how the Village Fund Unconditional Cash Transfer was administered in Jedong Cangkring Village, Prambanan District, Sidoarjo Regency, during the Covid-19 pandemic. The authors implemented a qualitative method with a descriptive approach for this study. This study examined indicators of effective policy implementation in the distribution of Village Fund Unconditional Cash Transfers in Jedong Cangkring Village, Prambon District, Sidoarjo Province. There are six indicators of successful implementation: (1) standards and policy objectives ; (2) resources; (3) inter-organizational relations; (4) characteristics of implementing agents; (5) social, economic, and political conditions, and (6) executor disposition or attitude. Village apparatuses, neighborhood leaders, and citizens who received Village Fund Unconditional Cash Transfers were used as informants for this study. The data for this study were collected through interviews, documentation, and literature reviews. The findings of this study indicate a number of issues regarding implementation indicators. Village Fund Unconditional Cash Transfer distribution needs to be brought back on track; there is a lack of coordination between the center and the village; and there is no role for NGOs as third parties in monitoring Village Fund Unconditional Cash Transfer distribution. The social, economic, and political conditions did not go according to plan, and there is also a problem with technology, as many elderly employees still struggle with it. On the other hand, policy implementers strive to adhere as closely as possible to regulations from above or the central government. Keywords: Village Fund Unconditional Cash Transfer, Policy Implementation, Covid-19 Pandemic.